Loss of Function of Rice Plastidic Glycolate/Glycerate Translocator 1 Impairs Photorespiration and Plant Growth - Shim, Su-Hyeon; Lee, Sang-Kyu; Lee, Dae-Woo; Brilhaus, Dominik; Wu, Guangxi; Ko, Sooyeon; Lee, Choon-Hwan; Weber, Andreas P.M.; Jeon, Jong-Seong (Frontiers in Plant Science, 2020)
Ribulose-1,5-bisphosphate carboxylase/oxygenase, the key enzyme of photosynthetic carbon fixation, is able to accept both O2 and CO2 as substrates. When it fixes O2, it produces 2-phosphoglycolate, which is detoxified by photorespiration and recycled to the Calvin-Benson-Bassham cycle. To complete photorespiration, metabolite transport across three organelles, chloroplast, peroxisome and mitochondria, is necessary through transmembrane transporters. In rice (Oryza sativa) little is known about photorespiratory transmembrane transporters. Here, we identified the rice plastidic glycolate/glycerate translocator1 (OsPLGG1), a homolog of Arabidopsis PLGG1. OsPLGG1 mutant lines, osplgg1-1, osplgg1-2 and osplgg1-3, showed a growth retardation phenotype, such as pale green leaf, reduced tiller number, and reduced seed grain weight as well as reduced photosynthetic carbon reduction rate due to low activities of photosystem I and II. The plant growth retardation in osplgg1 mutants was rescued under high CO2 condition. Subcellular localization of OsPLGG1-GFP fusion protein, along with its predicted N-terminal transmembrane domain, confirmed that OsPLGG1 is a chloroplast transmembrane protein. Metabolite analysis indicated significant accumulation of photorespiratory metabolites, especially glycolate and glycerate, which have been shown to be transported by the Arabidopsis PLGG1, and changes for a number of metabolites which are not intermediates of photorespiration in the mutants. These results suggest that OsPLGG1 is the functional plastidic glycolate/glycerate transporter, which is necessary for photorespiration and growth in rice.